Centralizer of braids and Fibonacci numbers - Ali, Usman; Haider, Azeem (Utilitas Mathematica, 2012)
The paper encloses computation of simple centralizer of simple braids and their connection with Fibonacci numbers. Planarity of some commuting graphs is also discussed in the last section.